Complex variables with Maple - Daud Mohamad (Penerbit Universiti Teknologi Mara, 2012)
Complex Variable With Maple is an introductory text for undergraduate students in Mathematics as a continuation of calculus. It covers the basic theory of complex variables consisting topics on complex numbers, complex functions, complex integration and series. This book provides numerous examples and illustrations for further understanding and also sufficient exercises for students to practices.